Herbal Therapeutics as Potential Prophylaxis for SARS-CoV-2 Infection - Singhal, Shipra; Kumar, Abhishek; Katiyar, Deepti; Patil, Vaishali M. (Natural Products Journal, The, 2023)
Introduction: The global pandemic COVID-19 and its uncontrolled spread and lack of effective therapeutics demand to investigate the herbal resources in search of novel, safe and potent therapeutics. Herbal medicines have proven the advantage of multi-target potential and thus can be investigated for virus-host interaction protein and viral protein targets. Objectives: The manuscript aims to provide an outcome-based analysis of studies performed to evaluate herbal compounds as anti-COVID agents. The studies focus on the proposed mechanism of viral inhibition by herbal compounds. Methods: The details on modern drug discovery approach for investigating potential antiviral agents include in silico screening, ADMET and molecular docking studies. It helps to establish the probable mechanism of viral inhibition as well as to establish pharmacophore. The reports explaining the role of herbal therapeutics/phytochemicals in antiviral drug development have been thoroughly searched. Results: The study summarizes herbal therapeutics and phytochemicals based on their antiviral properties against various pathogenic viruses. Herbal compounds that have an interesting role in the development of therapeutics and herd immunity against SARS-CoV-2 are included and discussed. Conclusion: The manuscript summarizes herbal resources and phytochemicals investigated as a potential therapeutic option for SARS-CoV-2 inhibition. It will be a useful resource for researchers interested in developing herbal therapeutics for the prevention and/or treatment of COVID-19.
Keywords: prophylaxis